Bacterial vaginosis in female facility workers in north-western Tanzania: prevalence and risk factors. Issue 5 (26th May 2009) - Baisley, K; Changalucha, J; Weiss, H A; Mugeye, K; Everett, D; Hambleton, I; Hay, P; Ross, D; Tanton, C; Chirwa, T; Hayes, R; Watson-Jones, D
Abstract : Objectives: To determine prevalence of, and risk factors for, bacterial vaginosis (BV) among herpes simplex virus (HSV) 2 seropositive Tanzanian women at enrolment into a randomised, placebo-controlled trial of HSV suppressive treatment. Methods: 1305 HSV-2 seropositive women aged 16–35 years working in bars, guesthouses and similar facilities were interviewed, examined and tested for HIV, syphilis, Neisseria gonorrhoeae, Chlamydia trachomatis, BV, candidiasis and trichomoniasis. Factors associated with BV were analysed using logistic regression to estimate odds ratios and 95% confidence intervals. Results: BV prevalence was 62.9%; prevalence of Nugent score 9–10 was 16.1%. Independent risk factors for BV were work facility type, fewer dependents, increasing alcohol consumption, sex in the last week (adjusted OR 2.03; 95% CI 1.57 to 2.62), using cloths or cotton wool for menstrual hygiene, HIV (adjusted OR 1.41; 95% CI 1.09 to 1.83) and Trichomonas vaginalis infection. There was no association between BV and the frequency or method of vaginal cleansing. However, BV was less prevalent among women who reported inserting substances to dry the vagina for sex (adjusted OR 0.44; 95% CI 0.25 to 0.75). Conclusion: BV was extremely prevalent among our study population of HSV-2 positive female facility workers in North-western Tanzania. Although recent sex was associated with increased BV prevalence, vaginal drying was associated with lower BV prevalence. Further studies of the effects of specific practices on vaginal flora are warranted.